2015
DOI: 10.13181/mji.v23i4.1067
|View full text |Cite
|
Sign up to set email alerts
|

Chronic thromboembolic pulmonary hypertension in young woman with history of caesarian section

Abstract: Chronic thromboembolic pulmonary hypertension (CTEPH) is one of subgroups of pulmonary hypertension. This is a serious medical condition that severely under diagnosed. CTEPH is commonly underdiagnosed due to non specific symptoms and lack of diagnostic tools. The aim of this presentation is to discuss the etiology, risk factors, diagnosis and management of CTEPH. A 36-year-old woman presented with easily fatigue and dyspneu on effort since two years ago. The symptom occured about three months after she gave bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Anterior precordial leads often show T wave inversion, which represents repolarization irregularities associated with right ventricular hypertrophy. 6 Although there may not be a consistent correlation between ECG findings and the severity of pulmonary PH, a study involving 47 patients reported that a R wave amplitude in V1 greater than 1.2 mV or an R/SV1 ratio exceeding 7 can indicate a pulmonary artery systolic pressure surpassing 90 mm Hg. The sensitivity of this indicator was found to be 94%, while the specificity was 47%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior precordial leads often show T wave inversion, which represents repolarization irregularities associated with right ventricular hypertrophy. 6 Although there may not be a consistent correlation between ECG findings and the severity of pulmonary PH, a study involving 47 patients reported that a R wave amplitude in V1 greater than 1.2 mV or an R/SV1 ratio exceeding 7 can indicate a pulmonary artery systolic pressure surpassing 90 mm Hg. The sensitivity of this indicator was found to be 94%, while the specificity was 47%.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Echocardiography is helpful because it may identify secondary conditions including left-sided heart disease, valvular abnormalities, chamber mass, or intracardiac shunt. 6,9 A diagnosis of CTEPH was made after the patient's echocardiogram indicated positive McConnell, positive D-Shaped left ventricle, moderate PH with a mPAP of 46 mmHg. Growing research has examined the CTPA's diagnostic accuracy for CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…A ventilation/perfusion scan (V/Q) is an important test for differentiating IPAH from chronic thromboembolic PH [ 14 ]. Underutilization of V/Q scans during the screening of PH patients might lead to misdiagnosis of PAH [ 14 ].…”
Section: Diagnosis Of Pah In Indonesia and Guideline Implementationmentioning
confidence: 99%
“…8 The other two articles in this issue are not less interesting, because they deal with widespread health problems in Indonesia, thalassemia and preeclampsia. 9,10 Since it is well known that thalassemia patients suffer from instability of their erythrocytes in blood circulation, it is very important to know, how far thalassemia trait of donors influences the stability of their stored blood. 9 Last but not least, we have a case of chronic thromboembolic pulmonary hypertension in a woman with history of Caesarian Section due to preeclampsia.…”
mentioning
confidence: 99%
“…9 Last but not least, we have a case of chronic thromboembolic pulmonary hypertension in a woman with history of Caesarian Section due to preeclampsia. 10 We hope that the collection of articles in this issue is a valuable finale of MJI. Volume 23, 2014 and we want to wish both our esteemed readers and our journal a successful and prosperous New Year, 2015.…”
mentioning
confidence: 99%